Non-verbal behavior of respondents as a source of additional information during polls (on the example of empirical stage of the project «Mass consciousness in the zone of military conflict in Donbas region») - Черевата, Д. Ю. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2019)
In this article the possibility and necessity of analysis of non-verbal reactions is considered on the example of the empirical stage of the project "Mass consciousness in the zone of military conflict in the Donbass". The main nonverbal manifestations of respondents in the sociological interview, the possibility of their interpretation, the complexity of recognition and the prospects of evaluation are analyzed. The focus is on the analysis of dynamics and gestures as a specific feature of the interviewer's work with the respondent during the interview. It is proposed to develop and create observation cards that will be added to the interviewer's questionnaire in order to assess the non-verbal behavior of respondents.